Multiple Jobholding: An Integrative Systematic Review and Future Research Agenda - Campion, Emily D.; Caza, Brianna B.; Moss, Sherry E. (Journal of Management, 2020)
Despite sizable but varying estimates of multiple jobholding (MJH) and decades of research across disciplines (e.g., management, economics, sociology, health and medicine), our understanding of MJH is rather limited. The purpose of this review is to provide a coherent synthesis of the literature on MJH, or working more than one job. Beginning with a discussion of the motivations and demographic predictors that forecast MJH, we note a distinct divide between the research that predicts MJH and the research that examines outcomes, with few studies exploring how motivations might relate to MJH experiences and outcomes. Another significant observation in this review is the inconsistency of findings across and within disciplines regarding whether MJH is depleting or enriching. Using this framework to organize our review, we attempt to reconcile the generally mixed results by presenting research on mechanisms and boundary conditions of MJH to explain how and when multiple jobholders (MJHers) are depleted or enriched. By integrating findings from the literature, we are able to articulate more clearly the paths of depletion and enrichment and discuss how push versus pull-based motivations to hold multiple jobs likely predict these pathways. Finally, we provide a strategic agenda highlighting areas where additional research is urgently needed to equip scholars with practical knowledge on how to help MJHers manage their multiple work roles and how to help organizations manage MJHers.